CMOS precision full-wave rectifier using current conveyor - Kumngern, Montree (My University, 2010)
This paper presents a precision full-wave rectifier, which is highly suitable for CMOS technology implementation. The system comprises a voltage-to-current converter, precision full-wave rectifiers and a current-to-voltage converter. An input voltage signal is converted into two symmetrical current signals by using a dual-output second generation current conveyor. Two current signals will be rectified by using junction diodes and convert into output voltages by using grounded MOS resistors. Simulated rectifier results based on a 0.5μm CMOS technology demonstrates very high operating frequency and very precise rectification. © 2010 IEEE.
Keywords: CCII; CMOS; Current-mode; Precision rectifier